2000
DOI: 10.1177/002246690003400105
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Issues in Special Education in Botswana

Abstract: The development of educational facilities for children with special educational needs has become a universal priority. The United Nations Educational, Scientific and Cultural Organization (1996) received information from 52 member states as to legislation pertaining to special needs education. Forty-eight countries (92.3% of the member states involved in the study) enacted legislation pertaining to special needs education, whereas the remaining four countries (7.7%) have active proposals. Globally, Botswana is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 1 publication
0
25
0
Order By: Relevance
“…Lesotho's neighbour, the Republic of South Africa, adopted an inclusive education policy only after the demise of apartheid (Republic of South Africa Department of Education, 2003). Botswana (a country in which many people from Lesotho share cultural and linguistic roots) has a balanced approach to special education by keeping special schools for students with disabilities that were introduced by missionaries and providing more inclusive approaches in government schools (Abosi, 2000).…”
Section: Inclusive Education In Lesothomentioning
confidence: 99%
“…Lesotho's neighbour, the Republic of South Africa, adopted an inclusive education policy only after the demise of apartheid (Republic of South Africa Department of Education, 2003). Botswana (a country in which many people from Lesotho share cultural and linguistic roots) has a balanced approach to special education by keeping special schools for students with disabilities that were introduced by missionaries and providing more inclusive approaches in government schools (Abosi, 2000).…”
Section: Inclusive Education In Lesothomentioning
confidence: 99%
“…Some teachers are posted there by some political influence and other personal interest, and not for the sake of the students. The result has provided empirical support to Abosi (1999) findings that persons with special needs are not well catered for by the government. Furthermore, the private schools being what it is seems to receive attention from private organizations, non-governmental organizations (NGOs), churches, communities and individuals, hence the more facilities.…”
Section: Discussion and Recommendationsmentioning
confidence: 55%
“…However, the study of Abosi (1999) showed that, the individuals with special needs are not well catered for by the government. He lamented that teachers' training and general development, for those with special needs is really lacking, especially in Africa.…”
Section: Introductionmentioning
confidence: 99%
“…There is a need for a revised Code of Ethics for teachers in Botswana to be applied to teachers who abuse children with disabilities in their schools (Abosi, 2000;Botswana Government, 1994). There is a need for a revised Code of Ethics for teachers in Botswana to be applied to teachers who abuse children with disabilities in their schools (Abosi, 2000;Botswana Government, 1994).…”
Section: Recommendationsmentioning
confidence: 99%
“…Currently, the Botswana Government provides free education, food and uniforms to children with disabilities in all provinces (Abosi, 2000;Tsheko, 2007). Despite the fact that the government is committed to the education of all children including those with disabilities, there is a need for an increase in free education for such children (Abosi, 2000;Tsheko, 2007). Those who go to private schools pay fees.…”
Section: Introductionmentioning
confidence: 99%